Silver-modified polyniobotungstate for the visible light-induced simultaneous cleavage of C–C and C–N bonds - Shujun Li; Na Li; Gang Li; Yubin Ma; Mengyao Huang; Qingchun Xia; Qianyi Zhao; Xuenian Chen (Polyoxometalates, 2023)
Silver-modified polyniobotungstate based on Nb/W mixed-addendum polyoxometalate with formula Ag9[P2W15Nb3O62]·21H2O (Ag-Nb/W) was synthesized and then characterized by various analytical and spectral techniques. Ag-Nb/W was proven to be an efficient photocatalyst for the oxidative ring opening of 2-phenylimidazo[1,2-a]pyridine via the simultaneous cleavage of C–C and C–N bonds. Under visible light (430–440 nm) and with oxygen as an oxidant at room temperature, Ag-Nb/W can catalyze the rapid transformation of various 2-phenylimidazo[1,2-a]pyridine derivatives to produce the corresponding oxidative ring-opening product N-(pyridin-2-yl) amides in good isolated yields ranging from 65% to 78%. As a heterogeneous photocatalyst, Ag-Nb/W showed excellent sustainability and recyclability in the recycling experiments. Infrared (IR) spectroscopy and X-ray diffraction (XRD) analysis indicated that Ag-Nb/W could retain its integrity after catalysis. A possible mechanism involving the singlet oxygen for the catalytic reaction was proposed.